ANALYSIS OF THE EFFECT OF FAN GANN AND SQUARE NINE IN THE FOREX MARKET (STUDY OF PERFORMANCE AND PROFITABILITY (XAUUSD)) - Luay Ali Mahmood; Anwar Mahmood Ghafoor; Muneeb Khalaf mhameed (Galaxy International Interdisciplinary Research Journal, 2024)
Gann angles and the square of nine for technical analysis are tools for tracking prices and determining the price trend for currency pairs. Gann angles are considered as a trend line, meaning the price direction, and when the price angles intersect, a price reversal occurs, and the square of nine for determining entry and price reversal areas, helps traders speculate in the markets. Different types such as (Forex), the stock market (Crypto), and other financial markets, Using programs that display price charts and technical analysis tools help in drawing the current path taken by the price (rise, width, decline) and determine for them the current location that the price has reached when combining more than one strategy, giving the market a clear future vision that helps traders make the best decision, and is The appropriate decision that suits the price location is the high decision (buy) or low decision (sell), and the occasional decision (wait), taking into account reducing the risks for those decisions and managing the capital.